2004
DOI: 10.1104/pp.104.046482
|View full text |Cite
|
Sign up to set email alerts
|

The Potassium-Dependent Transcriptome of Arabidopsis Reveals a Prominent Role of Jasmonic Acid in Nutrient Signaling  

Abstract: Full genome microarrays were used to assess transcriptional responses of Arabidopsis seedlings to changing external supply of the essential macronutrient potassium (K+). Rank product statistics and iterative group analysis were employed to identify differentially regulated genes and statistically significant coregulated sets of functionally related genes. The most prominent response was found for genes linked to the phytohormone jasmonic acid (JA). Transcript levels for the JA biosynthetic enzymes lipoxygenase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

40
410
5
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 441 publications
(464 citation statements)
references
References 111 publications
40
410
5
9
Order By: Relevance
“…In a classic study, Drew (1975) showed an increase in overall lateral root (LR) growth of barley seedlings, even when K was supplied only to parts of the root system. Conversely, a typical response of Arabidopsis (Arabidopsis thaliana) Columbia (Col-0) seedlings to low K is the drastic reduction of LR elongation (Armengaud et al, 2004;Shin and Schachtman, 2004). Conflicting data have been published on the effect of low K on main root (MR) growth in the same species, ranging from no effect (Shin and Schachtman, 2004) to impaired MR elongation (Jung et al, 2009;Kim et al, 2010).…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…In a classic study, Drew (1975) showed an increase in overall lateral root (LR) growth of barley seedlings, even when K was supplied only to parts of the root system. Conversely, a typical response of Arabidopsis (Arabidopsis thaliana) Columbia (Col-0) seedlings to low K is the drastic reduction of LR elongation (Armengaud et al, 2004;Shin and Schachtman, 2004). Conflicting data have been published on the effect of low K on main root (MR) growth in the same species, ranging from no effect (Shin and Schachtman, 2004) to impaired MR elongation (Jung et al, 2009;Kim et al, 2010).…”
mentioning
confidence: 93%
“…Conflicting data have been published on the effect of low K on main root (MR) growth in the same species, ranging from no effect (Shin and Schachtman, 2004) to impaired MR elongation (Jung et al, 2009;Kim et al, 2010). Some components involved in K starvation responses have been identified, such as jasmonates (Armengaud et al, 2004(Armengaud et al, , 2010, reactive oxygen species (Shin and Schachtman, 2004), and ethylene (Jung et al, 2009). However, the molecular identity of a root K sensor acting at the base of the signaling cascade is so far unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They further noted that the increase in ADC activity, induced by K ' deficiency, did not appear to involve changes in mRNA or protein abundance, suggesting the post-translational regulation mechanism for ADC activation. Recently, full genome microarrays were used to assess transcriptional responses of Arabidopsis seedlings to changing external supply of K ' (Armengaud et al 2004). The physiological rationale for Put increase is unclear.…”
Section: Nutrient Deficiencymentioning
confidence: 99%
“…Although cellular and tissue K + -homeostasis can protect metabolically active cells from serious K + -deficiency for a limited period of time, it is clear that a plant that experiences long-term K + -deficiency will have to re-prioritise its growth, development and metabolism to achieve maximal seed production with limited resources. Research in our lab has identified jasmonic acid (JA) as a potential central integrator of the adaptation process [9]. Microarray analysis showed that a large percentage of the K + -responsive transcriptome is related to JA, and a rise of JA during K + -deficiency, as well as the specificity of this response for K + -deficiency, have since been confirmed [A Amtmann, P Armengaud, unpublished data].…”
mentioning
confidence: 97%